The cultural background of judges as an influence on judicial decision-making: a theoretical discussion - Basabe-Serrano, Santiago (2025)
This paper reviews how judges’ values, attitudes, and culture influence their judicial decisions by exploring the origins and current trends in judicial behavior studies. It highlights significant empirical contributions and underscores the importance of a multidisciplinary approach to thoroughly analyze court rulings using qualitative and quantitative tools to understand the underlying rationality in judicial decision-making.